Religion and Sustainability Social Movements and the Politics of the Environment. - Johnston, Lucas F. (Hoboken : Taylor and Francis, 2014)
Sustainability is now key to international and national policy, manufacture and consumption. It is also central to many individuals who try to lead environmentally ethical lives. Historically, religion has been a significant part of many visions of sustainability. Pragmatically, the inclusion of religious values in conservation and development efforts has facilitated relationships between people with different value structures. Despite this, little attention has been paid to the interdependence of sustainability and religion, and no significant comparisons of religious and secular sustainabili.
6. The contributions of natural and social sciences to the religious dimensions of sustainabilityPart III: The Ethnographic Data and Sustainability Cases; 7. Walking together separately: evangelical creation care; 8. Stories of partnership: interfaith efforts toward sustainability; 9. The religious dimensions of secular sustainability; 10. Manufacturing or cultivating common ground?; Notes; Bibliography; Index
Description based upon print version of record.
Keywords: Environmental ethics; Environmental justice; Religion and politics; Sustainability -- Religious aspects; Environmental ethics; Environmental justice; Religion and politics; Sustainability -- Religious aspects; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books